English Teachers’ Perspective on Feedback in Merdeka Curriculum - Natalia, Putu Rosa; Padmadewi, Ni Nyoman; Utami, I. G. A. Lokita Purnamika (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to investigate teachers' perspectives on feedback in English language learning, especially in the Merdeka Curriculum. Three English teachers who teach at Junior High School were interviewed regarding their perspective on feedback, challenges in implementing feedback, and their views on the role of feedback in emphasizing the values of Pancasila Student Profile. A simple qualitative method was used in this study. The procedure includes data collection, data reduction, data display, and drawing conclusions from Miles et al. (2014) were used in this study. The study results show that teachers had a positive perspective on feedback; teachers stated that students' improvement, motivation, and progress are the main reasons they provide feedback. The teacher considered that the choice of words is essential in giving feedback. Meanwhile, time limitations are an obstacle for teachers in providing feedback. Also, teachers agree that feedback emphasizes the value of student independence by emphasizing students to be more independent in their respective learning processes. Also, teachers stated that feedback train students critical thinking as well as giving students the opportunity to make better progress and avoid making the same mistakes in their learning.